The Study Of Physiochemical Properties And Spraying Characteristics Of Hybrid Biofuel For Compression Ignition (CI) Engine Application - Fadzil, Mohammad Azhar (Universiti Sains Malaysia, 2018)
Straight vegetable oil (SVO) biofuels is one of potentially alternative petroleum diesel fuel due to its comparable physical properties to that petroleum diesel fuel. However, the high viscosity and density of SVO limits their direct application in a CI engine. Therefore, to solve this problem, hybrid biofuels were introduced to reduce the viscosity and density of SVO. In this study, biofuel of higher chain alcohol (butanol and pentanol) was blended together with Refined Palm Oil (RPO). A total of five blends with the mixing ratios of 10%, 20%, 30%, 40% and 50% of both alcohols were prepared. Key properties of the fuel such as kinematic viscosity, calorific value and density of the blends were measured and benchmarked against the biodiesel standards based on ASTM D6751. It was found that viscosity, density and calorific value of the blends decreased with the increase of alcohols fraction. Optimized blends which were 50BUT50RPO and 53PEN47RPO have a comparable physiochemical properties to that diesel fuel. The optimized blends were studied in term of their spraying characteristic in a common rail injection system. The spray characteristics of optimized blends were captured and measured. Both blends have a comparable spray penetration at 1000 bar injection pressure. Meanwhile, the spray angle and width of optimized blends were smaller in comparison with diesel-based fuel. This is due to the comparatively higher viscosity and surface tension of hybrid biofuel blends, which enhanced the friction effect between fuel and the injector nozzle surface and inhibited the breakup of the liquid jet. Overall, both 50BUT:50RPO and 53PEN:47RPO have a comparable physiochemical properties and spraying characteristic in comparison with diesel-based fuel. Hence both hybrid biofuel blends can be used for a compression ignition (CI) engine application.